1993
DOI: 10.7326/0003-4819-119-12-199312150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Morbidity Associated with Long-Term Use of Venous Access Devices in Patients with Cancer

Abstract: The incidence of infections per device-day was 12 times greater with catheters than with ports. Patients with solid tumors were the least likely to have device-related infectious morbidity compared with those with hematologic cancers. The reasons for the difference in infectious complications is uncertain but may be attributable to type of disease, intensity of therapy, frequency with which devices are accessed, or duration of neutropenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
183
3
20

Year Published

1995
1995
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(220 citation statements)
references
References 0 publications
14
183
3
20
Order By: Relevance
“…However, in a randomized study of infectious morbidity in patients with solid tumors, chemoports were shown to be associated with fewer infections than other catheters [8]. Compared with catheters, chemoports are irrigated less frequently, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a randomized study of infectious morbidity in patients with solid tumors, chemoports were shown to be associated with fewer infections than other catheters [8]. Compared with catheters, chemoports are irrigated less frequently, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, CVC-related episodes accounted for 40% of episodes in patients receiving allogeneic BMT, but only 8% in patients receiving autologous BMT (P Ͻ 0.001). This particular aspect could be due to the fact that patients undergoing allogeneic BMT use CVC, for a longer period because of the complexity of their management in the post-transplant period (eg for control of GVHD or CMV infection) and are therefore exposed to major risk because of the frequent necessity for venous access, [10][11][12][13] perhaps by parents at home. 13,14 However, we have no data to support this supposition.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Although TIVAPS are generally associated with a lower long-term risk of infection compared to Hickman-type central venous catheters, [3,4] complications during their placement and long-term use are still a matter of concern. These complications, including infection, catheter fracture, thrombosis and extravasation [5,6,7], may necessitate device replacement, resulting in additional patient stress and treatment delays.…”
Section: Introductionmentioning
confidence: 99%